Surgical Procedures for External Auditory Canal Carcinoma and the Preservation of Postoperative Hearing - Hiroshi Hoshikawa; Takenori Miyashita; Nozomu Mori (Case Reports in Surgery)
Carcinoma of the external auditory canal (EAC) is an unusual head and neck malignancy. The pathophysiology of these tumors is different from other skin lesions because of their anatomical and functional characteristics. Early-stage carcinoma of the EAC can be generally cured by surgical treatment, and reconstruction of the EAC with a tympanoplasty can help to retain hearing, thus improving the patients’ quality of life. In this study, we present two cases of early-stage carcinoma of the EAC treated by canal reconstruction using skin grafts after lateral temporal bone resection. A rolled-up skin graft with a temporal muscle flap was useful for keeping the form and maintaining the postoperative hearing. An adequate size of the skin graft and blood supply to the graft bed are important for achieving a successful operation.